2021
DOI: 10.3329/brc.v8i1.57042
|View full text |Cite
|
Sign up to set email alerts
|

All four dengue virus serotypes co-circulate in concurrent dengue infections in a single dengue session in Chittagong, Bangladesh

Abstract: Purposes: Dengue fever, a mosquito-borne viral disease, is a global public health burden affecting millions of people each year and over 40% of world populations are at risk of dengue. Therefore, prompt and accurate dengue diagnosis is inevitable for disease surveillance and for aiding disease management. In this study we report dengue virus (DENV) seroprevalence in Chittagong, Bangladesh along with clinical manifestation of dengue infections. Methods: All samples included in this study were selected based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…This is perhaps originated from the inherent sequences of very similar but distinctive four DENV serotypes [15]. The typical clinical signs and symptoms of dengue disease include undifferentiated high fever, vomiting, musculoskeletal pain, myalgia, re-o-pain, rash, nausea, and headache which were observed in almost all cases of DENV infections [16] [Table 1]. A detail analysis indicated that DENV1 and DENV2 result very similar patterns of clinical symptoms which were quite different from those caused by DENV3 and DENV4, for example, ache-pain and diarrhea were absent in DENV3 and DENV4 infections, respectively [16].…”
Section: Dengue Disease and Dengue Virus Serotypementioning
confidence: 99%
See 3 more Smart Citations
“…This is perhaps originated from the inherent sequences of very similar but distinctive four DENV serotypes [15]. The typical clinical signs and symptoms of dengue disease include undifferentiated high fever, vomiting, musculoskeletal pain, myalgia, re-o-pain, rash, nausea, and headache which were observed in almost all cases of DENV infections [16] [Table 1]. A detail analysis indicated that DENV1 and DENV2 result very similar patterns of clinical symptoms which were quite different from those caused by DENV3 and DENV4, for example, ache-pain and diarrhea were absent in DENV3 and DENV4 infections, respectively [16].…”
Section: Dengue Disease and Dengue Virus Serotypementioning
confidence: 99%
“…The typical clinical signs and symptoms of dengue disease include undifferentiated high fever, vomiting, musculoskeletal pain, myalgia, re-o-pain, rash, nausea, and headache which were observed in almost all cases of DENV infections [16] [Table 1]. A detail analysis indicated that DENV1 and DENV2 result very similar patterns of clinical symptoms which were quite different from those caused by DENV3 and DENV4, for example, ache-pain and diarrhea were absent in DENV3 and DENV4 infections, respectively [16]. However, the number of samples analyzed in each category was very limited, therefore, vast number samples from different geolocations are worth considering for developing rationale for infecting DENV serotypes with clinical signs and symptoms of dengue infection.…”
Section: Dengue Disease and Dengue Virus Serotypementioning
confidence: 99%
See 2 more Smart Citations
“…There have been various reports from tropical and subtropical countries across the world of patients testing positive for heterosubtypic dengue infections 18 19 20 21 22 23 24 25 26 27 28 .…”
Section: Introductionmentioning
confidence: 99%